Pengaruh Pengungkapan Laporan Keberlanjutan Terhadap Harga Saham (Studi Empiris pada Perusahaan yang Menerbitkan Laporan Keberlanjutan dan Terdaftar di Bursa Efek Indonesia Tahun 2012 – 2014) - Arif Rakhman; Heikal Muhammad Zakaria; Suhono Suhono (Accounthink, 2019)
The purpose of this research is to prove if any effect of Sustainability report on stock price. Sustainability report disclosure by the company is still rare because there is no standard assessment and also the company still considers this sustainability report is not very important for investors. Sustainability report assessment according to Global Reporting Initiative (GRI). The effect of Sustainability report disclosure measured by the total CSR disclosure score of each dimension based on GRI guideline in company’s annual reports . Hypothesis testing was performed using a regression model with a sample of 15 companies listed on the BEI consistently issuing sustainability reports using GRI guidelines during 2012-2014. The results of the research give empirical evidence that sustainabilty report disclosure have positive and significant effect on price. This study is useful for companies to know the benefits of issuing sustainability reports and also for investors to find out whether the shares of the companies issuing the sustainability report are worth or not.